Use and clinical efficacy of standard and health information technology fall risk assessment tools. (4th December 2017) - Teh, Ruth C; Wilson, Anne; Ranasinghe, Damith; Visvanathan, Renuka
Abstract : Objective: To evaluate the health information technology (HIT) compared to Fall Risk for Older Persons (FROP) tool in fall risk screening. Methods: A HIT tool trial was conducted on the geriatric evaluation and management (GEM, n = 111) and acute medical units (AMU, n = 424). Results: Health information technology and FROP scores were higher on GEM versus AMU, with no differences between people who fell and people who did not fall. Both score completion rates were similar, and their values correlated marginally (Spearman's correlation coefficient 0.33, P < 0.01). HIT and FROP scores demonstrated similar sensitivity (80 vs 82%) and specificity (32 vs 36%) for detecting hospital falls. Hospital fall rates trended towards reduction on AMU (4.20 vs 6.96, P = 0.15) and increase on GEM (10.98 vs 6.52, P = 0.54) with HIT tool implementation. Conclusions: Health information technology tool acceptability and scoring were comparable to FROP screening, with mixed effects on fall rate with HIT tool implementation. Clinician partnership remains key to effective tool development.